Central and Peripheral Peptides Regulating Eating Behaviour and Energy Homeostasis in Anorexia Nervosa and Bulimia Nervosa: A Literature Review. (18th June 2014) - Tortorella, Alfonso; Brambilla, Francesca; Fabrazzo, Michele; Volpe, Umberto; Monteleone, Alessio Maria; Mastromo, Daniele; Monteleone, Palmiero
Abstract A large body of literature suggests the occurrence of a dysregulation in both central and peripheral modulators of appetite in patients with anorexia nervosa (AN) and bulimia nervosa (BN), but at the moment, the state or trait‐dependent nature of those changes is far from being clear. It has been proposed, although not definitively proved, that peptide alterations, even when secondary to malnutrition and/or to aberrant eating behaviours, might contribute to the genesis and the maintenance of some symptomatic aspects of AN and BN, thus affecting the course and the prognosis of these disorders. This review focuses on the most significant literature studies that explored the physiology of those central and peripheral peptides, which have prominent effects on eating behaviour, body weight and energy homeostasis in patients with AN and BN. The relevance of peptide dysfunctions for the pathophysiology of eating disorders is critically discussed. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.